2004
DOI: 10.4161/cbt.3.1.547
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1, An Oxygen and Metal Responsive Transcription Factor

Abstract: Normal development and function of metazoan organisms depend on oxygen availability. The level of oxygen can be sensed by individual cells, which respond to reduced oxygenation (hypoxia) largely through activation of hypoxia-inducible factor-1 (HIF-1). At the organism level the response to hypoxia involves an increase in red blood cell production. Within tissues, HIF activation increases the blood supply and blood vessel growth. At the individual cell level it is manifested as an increase in anaerobic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 74 publications
10
196
2
3
Order By: Relevance
“…The level of signal caused by 0.25 mM NiSO 4 was comparable with the signal produced by 0.25 mM CoCl 2 ; at 0.5 mM NiSO 4 , the signal was almost doubled. It was shown previously that exposure to nickel(II) or cobalt(II) stabilizes HIF␣ and increases HIF-1-dependent transcription (10). Indeed, transfection of the HRE-Luc reporter showed a dose-dependent induction of HIF-dependent transcription in nickel(II)-and cobalt(II)-exposed 1HAEoϪ cells (Fig.…”
Section: Effect Of Nickel(ii) or Cobalt(ii) On Hydroxylation Of Pro-4supporting
confidence: 52%
See 2 more Smart Citations
“…The level of signal caused by 0.25 mM NiSO 4 was comparable with the signal produced by 0.25 mM CoCl 2 ; at 0.5 mM NiSO 4 , the signal was almost doubled. It was shown previously that exposure to nickel(II) or cobalt(II) stabilizes HIF␣ and increases HIF-1-dependent transcription (10). Indeed, transfection of the HRE-Luc reporter showed a dose-dependent induction of HIF-dependent transcription in nickel(II)-and cobalt(II)-exposed 1HAEoϪ cells (Fig.…”
Section: Effect Of Nickel(ii) or Cobalt(ii) On Hydroxylation Of Pro-4supporting
confidence: 52%
“…Exposure to nickel(II) or cobalt(II) results in accumulation of HIF-1␣ and up-regulation of hypoxia-inducible genes in cells even in the presence of oxygen (8,17,21,22). This phenomenon has been described as "metal-induced hypoxia" (10). We investigated the mechanism of inhibition of prolyl hydroxylase activity and HIF-1 induction in human lung cells following nickel(II) or cobalt(II) exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under hypoxic conditions, by contrast, PHD activity is suppressed, leading to nuclear accumulation of HIF-1α and transcriptional induction of its target genes [50,51]. In addition to hypoxia, Ni and Co ions also mediate HIF-1α activation, as these metal ions can substitute for Fe 2+ at the Fe 2+ -binding site of PHDs, thereby inhibiting these enzymes [52,53]. Consistent with that effect, we found that the presence of Ni 2+ led to HIF-1α activation and induction of HIF-1α target genes in cultured SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which Co 2+ activates hypoxia inducible factor-1 (HIF-1) and mimics hypoxia in cells may be by substitution for Fe 2+ in the regulatory dioxygenase to inactivate the enzyme [8]. In lung cells, the underlying mechanism of cobalt-induced pneumotoxic effect was suggested by the down-regulation of the negative regulators of HIF-1 [9].…”
Section: Introductionmentioning
confidence: 99%